Analisis Ketahanan Energi Perkotaan di Provinsi Lampung dengan Metoda 4a (Studi Kasus: Kota Bandar Lampung, Kota Metro, dan Kabupaten Lampung Selatan) - Yudha Rahman; Citra Persada; Asirin Asirin (Universitas Batanghari Jambi, 2019)
Energy independence and national energy security are the objectives of the energy management policy regulated in Law No. 30 of 2007 on Energy. Energy security is illustrated by the 4A indicator, including its availability (availability), accessibility, affordability, and acceptability. From the condition of Energy Indonesia problem, it is necessary to study that can describe the condition of consumption and energy security for Lampung Province and share various alternative accomplishments. In this study were taken in 3 cities including Lampung Province namely Bandar Lampung City, Metro City, and South Lampung Regency. The purpose of this research is to analyze Urban Energy Security in Lampung Province with 4A Method (Availability, Accessibility, Affordability, and Acceptability) with Case Study of Bandar Lampung City, Metro City, and South Lampung Regency. The research method used is descriptive qualitative research in describing and describe the energy security. From the Availability research decrease, the accessibility is not stable yet, in terms of affordability of lack of standard price information, and in terms of Acceptability there is still doubt in the community about the quality of fuel and electricity consumed